Denotasi Dan Konotasi Dalam Lirik Lagu To The Bone Karya Pamungkas - Prasasti, Muhammad Pandu (PT. Alahyan Publisher Sukabumi, 2023)
This study aims to explain the meaning of denotation and connotation in the lyrics of the song To The Bone created by Pamungkas. There are two formulations of problems in this study, the first is how the meaning of the denotation in the lyrics of the song To The Bone created by Pamungkas, and the second is how the meaning of the connotation in the lyrics of the song To The Bone created by Pamungkas. Researchers use descriptive qualitative approach research methods in this study, which aims to find out the meaning of connotations and denotations contained in sentences from the lyrics of the songs sung by Pamungkas. The data collection technique used by researchers is the sentence expression analysis technique. Researchers use semiotic analysis techniques to analyze the data. From the data that has been found and studied, researchers concluded that the meaning of the denotation in the lyrics of the song To The Bone created by Pamungkas tells the story of a man who is very, very fond of a woman where the liking is felt to his bones. In the lyrics of the song To The Bone there is also a connotation meaning, the meaning of the connotation is about a man's liking that is very deep for a woman, Pamungkas also expresses an expression using a sentence in the lyrics of this song